Determinants of economic growth in Africa: An econometric assessment in the framework of the sustainable development goals - ALI, Walid; ABIDA, Zouheir (The International tax journal, 2025)
The race for inclusive development has led researchers to rethink the drivers of growth to achieve the Sustainable Development Goals (SDGs). This research note aims to explore the determinants of growth in Africa after analyzing the reference literature to select the explanatory variables. We examined growth in a panel of 54 countries belonging of the African continent using the generalized method of moment system estimators (GMM-sys) enter 2012 and 2022, controlling for idiosyncratic individual effects of countries with fixed-effects models. The use of GMM-sys to estimate growth patterns is not new, and many previous studies have used this appropriate approach for growth analyses. Based on the time series data collected and the estimation methodology used, the results show the determinants of African growth, and our results can have an implication for managers and policymakers interested in African emerging markets. Real GDP per capita with an order of delay is the most important variable in all models and we are expected to. In addition, we emphasize the importance of a strong governance and business environment in African countries to achieve the SDGs.